A systematic approach to bicontinuous cubic phases in ternary amphiphilic systems - Schwarz, Ulrich S.; Gompper, Gerhard (Arxiv, 2017)
The Fourier approach and theories of space groups and color symmetries are used to systematically generate and compare bicontinuous cubic structures in the framework of a Ginzburg-Landau model for ternary amphiphilic systems. Both single and double structures are investigated; they correspond to systems with one or two monolayers in a unit cell, respectively. We show how and why single structures can be made to approach triply periodic minimal surfaces very closely, and give improved nodal approximations for G, D, I-WP and P surfaces. We demonstrate that the relative stability of the single structures can be calculated from the geometrical properties of their interfaces only. The single gyroid G turns out to be the most stable bicontinuous cubic phase since it has the smallest porosity. The representations are used to calculate distributions of the Gaussian curvature and 2H-NMR bandshapes for C(P), C(D), S, C(Y) and F-RD surfaces.
Gesehen am 18.12.2017